Utilizing T-Lymphocyte Activation-Related Cytokines to Predict Non-Responsiveness to Treatment in Pediatric Kawasaki Disease - Ye B; Xiao J; Zhang C (Pediatric Health, Medicine and Therapeutics)
Bei Ye,1 Jiying Xiao,2 Caiyun Zhang3 1Department of Pediatrics, Hangzhou Children’s Hospital, Hangzhou, Zhejiang, People’s Republic of China; 2Department of Respiratory Medicine, Hangzhou Children’s Hospital, Hangzhou, Zhejiang, People’s Republic of China; 3Department of Pediatric Intensive Care Unit, Hangzhou Children’s Hospital, Hangzhou, Zhejiang, People’s Republic of ChinaCorrespondence: Caiyun Zhang, Department of Pediatric Intensive Care Unit, Hangzhou Children’s Hospital, Hangzhou, Zhejiang, People’s Republic of China, Email zcyzwj@163.comObjective: To investigate the predictive value of T-lymphocyte activation-related cytokines in non-responsive Kawasaki disease.Methods: Eighty-two children with Kawasaki disease, hospitalized from June 2022 to December 2023, were divided into two groups based on treatment response: the sensitive Kawasaki disease group (n=71) and the non-responsive Kawasaki disease group (n=11). Serum levels of T-lymph activation-related cytokines, including interleukin-2, 6, 7, 12, 15, 17, and tumor necrosis factor alpha, were measured before and after IVIG treatment in both groups. The differences in cytokine levels between the two groups were compared pre- and post-treatment. The ability of these cytokines to discriminate non-responsive Kawasaki disease was evaluated using ROC curves to determine the cut-off value.Results: Before initial treatment, IL-2, IL-6, IL-7, IL-12, IL-15, IL-17, and tumor necrosis factor-α values were significantly higher in the non-responsive Kawasaki disease group compared to the sensitive Kawasaki disease group. Comparisons before and after initial treatment showed significant decreases in IL-6 and 17 in the sensitive Kawasaki disease group and significant decreases in IL-6 and 7 in the non-responsive Kawasaki disease group. IL-6 and 17 significantly increased in the sensitive group compared to the non-responsive group after initial treatment. The ROC curves indicated that IL-6 predicted the area under the curve (AUC) for non-responsive Kawasaki disease to be 0.859 before treatment and 0.920 after treatment. Similarly, IL-17 had AUC values of 0.699 before treatment and 0.884 after treatment.Conclusion: Reassessing IL-6 and IL-17 following the initial treatment for Kawasaki disease may improve early warning signals for unresponsive Kawasaki disease.Keywords: Kawasaki disease, unresponsive Kawasaki disease, cytokines, T-lymphocyte activation, immunoglobulin